2022
DOI: 10.3349/ymj.2022.63.2.148
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Anti-Tumor Necrosis Factor-Alpha Agents for Patients with Intestinal Behcet’s Disease: A Systematic Review and Meta-Analysis

Abstract: Purpose Intestinal Behcet’s disease (BD) is a systemic autoimmune disease for which treatment options are limited. As a prospective therapeutic strategy for intestinal BD, anti-tumor necrosis factor-alpha (anti-TNF-α) agents have received increasing attention. In this study, we conducted a systematic review and meta-analysis to evaluate the efficacy and safety of anti-TNF-α agents for patients with intestinal BD. Materials and Methods We searched PubMed, Embase, and Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Based on reports of the 5‐year course of intestinal BD, 74.6% of patients experience remission or mild disease activity, and 16.2% have multiple relapses or chronic symptoms 8 . Similar to inflammatory bowel disease (IBD), intestinal BD can present with perforation, peritonitis, or severe lower gastrointestinal bleeding requiring medical acceleration, intestinal surgery, hospitalization, or emergency room visits 9–13 . In a 10‐year follow‐up study, there were no differences in the cumulative probabilities of intestinal surgery, hospitalization, recurrence, and reoperation rates between Crohn's disease (CD) ( n = 332) and intestinal BD ( n = 276) 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on reports of the 5‐year course of intestinal BD, 74.6% of patients experience remission or mild disease activity, and 16.2% have multiple relapses or chronic symptoms 8 . Similar to inflammatory bowel disease (IBD), intestinal BD can present with perforation, peritonitis, or severe lower gastrointestinal bleeding requiring medical acceleration, intestinal surgery, hospitalization, or emergency room visits 9–13 . In a 10‐year follow‐up study, there were no differences in the cumulative probabilities of intestinal surgery, hospitalization, recurrence, and reoperation rates between Crohn's disease (CD) ( n = 332) and intestinal BD ( n = 276) 14 .…”
Section: Introductionmentioning
confidence: 99%
“…8 Similar to inflammatory bowel disease (IBD), intestinal BD can present with perforation, peritonitis, or severe lower gastrointestinal bleeding requiring medical acceleration, intestinal surgery, hospitalization, or emergency room visits. [9][10][11][12][13] In a 10-year follow-up study, there were no differences in the cumulative probabilities of intestinal surgery, hospitalization, recurrence, and reoperation rates between Crohn's disease (CD) (n = 332) and intestinal BD (n = 276). 14 Conversely, several studies have reported that prognosis is worse in intestinal BD than in CD.…”
Section: Introductionmentioning
confidence: 99%
“…Response to infiximab was evident within 2 weeks and was maintained thereafter and repeat colonoscopies showed significant mucosal healing. Three different meta-analyses coming from China provide further support for the efficacy and acceptable safety of adalimumab and infliximab in the treatment of intestinal involvement of BS (95)(96)(97).…”
Section: Tnf-α Inhibitorsmentioning
confidence: 92%
“…Nevertheless, there remains a risk of disease recurrence, exacerbation of gastrointestinal bleeding, venous thrombosis, and infection[ 58 , 59 ]. Tumour necrosis factor-α (TNF-α) inhibitors, such as infliximab and adalimumab, are often used to treat severe and refractory cases of intestinal BD[ 60 , 61 ]. Patients with intestinal BD localized outside the ileocecal region may also have a greater need for anti-TNF-α immunotherapy[ 56 ].…”
Section: Medical Treatment Of Intestinal Bdmentioning
confidence: 99%